Microwave Power Beaming using Ka-band Radar - Haugstad, Travis; Nielsen, Joel (Proceedings of the Wisconsin Space Conference, 2016)
Power is transferred wirelessly from a ground based microwave transmitter to a receiver flown on a platform attached to a tethered aerostat. The signal is analyzed using consumer radar detection hardware and developed circuitry. This signal is analyzed by a programmable microcontroller, or Arduino, and data is then transmitted to a logging computer on the ground via flight computer and base station. Eventually, a rectenna and receiver will be developed to convert the microwaves to a useable voltage to power on-board instruments. This technology could be employed as a means to reduce the need for on-board power supplies for CubeSats deployed by the International Space Station, on orbit solar power generation, solar power satellites, etc.